Supporting Decision-Making with the Tools of Risk Management - Fekete, István (Public Finance Quarterly, 2022)
This year the Directives (hereinafter referred to as: Directives) to implement Act CXXII of 2009 and Government Decree 339/2019 on the internal control system of companies in public ownership were issued. One focal element of the internal control system is illuminated in the first part of the study in detail, based on the theoretical background of establishing the risk management system and the relevant standards and academic literature. It turns out from the first part that the key added value of risk management is the support given to decisions made at different levels. The study therefore presents a potential approach to demonstrate how risk management may be used efficiently to support strategic and project level decision-making, if there are no past data available, or not in sufficient quantity. In the second part of the study the author shows the experiences of the implementation of the risk management system - pursuant to the Directives - via the example of a large company. Relying partly on this and using his own experiences of many years the author specifies the factors supporting and hindering the implementation of the risk management system. According to his intention, the author specifies messages that may be helpful to practising experts to avoid the detection, evaluation and management of risks becoming administrative tasks. They must instead contribute to the longterm successful operation of the using organisation.